Seasonal dietary shifts enhance parasite transmission to lake salmonids during ice cover - Prati, Sebastian; Henriksen, Eirik Haugstvedt; Knudsen, Rune; Amundsen, Per-Arne (Ecology and Evolution, 2020)
Changes in abiotic and biotic factors between seasons in subarctic lake systems are often profound, potentially affecting the community structure and population dynamics of parasites over the annual cycle. However, few winter studies exist and interactions between fish hosts and their parasites are typically confined to snapshot studies restricted to the summer season whereas host‐parasite dynamics during the ice‐covered period rarely have been explored. The present study addresses seasonal patterns in the infections of intestinal parasites and their association with the diet of sympatric living Arctic charr ( Salvelinus alpinus ) and brown trout ( Salmo trutta ) in Lake Takvatn, a subarctic lake in northern Norway. In total, 354 Arctic charr and 203 brown trout were sampled from the littoral habitat between June 2017 and May 2018. Six trophically transmitted intestinal parasite taxa were identified and quantified, and their seasonal variations were contrasted with dietary information from both stomachs and intestines of the fish. The winter period proved to be an important transmission window for parasites, with increased prevalence and intensity of amphipod‐transmitted parasites in Arctic charr and parasites transmitted through fish prey in brown trout. In Arctic charr, seasonal patterns in parasite infections resulted mainly from temporal changes in diet toward amphipods, whereas host body size and the utilization of fish prey were the main drivers in brown trout. The overall dynamics in the community structure of parasites chiefly mirrored the seasonal dietary shifts of their fish hosts.